Mediasi sebagai upaya penyelesaian sengketa perceraian di pengadilan agama - Arifin, Muhammad Nur (Maliki Interdisciplinary Journal, 2025)
Divorce is a complex family legal issue requiring effective resolution mechanisms such as mediation. This study examines the role and strategies of mediators in improving mediation success rates for divorce cases at the Jombang Religious Court in 2025. Using an empirical legal approach with descriptive-analytical methods, data was collected through mediator interviews and reviews of literature and regulations. Findings show that mediation success rates remain low due to low public legal awareness, lack of goodwill from parties, insufficient mediator competency, and inadequate facilities. However, a positive trend was observed in partial successes, such as agreements on child custody and asset division. Effective strategies included active communication, reframing techniques, empathetic humanistic approaches, and integration of religious values. To enhance mediation quality, improvements in mediator training, facilities, and public awareness are essential. Professionally managed mediation serves not only as a formal procedure but also as a restorative justice tool to reduce conflict and maintain family harmony.